Nanosystems for chemodynamic based combination therapy: Strategies and recent advances - Li, Minghui; Zhang, Wen; Xu, Xiaopeng; Liu, Guoying; Dong, Mengfei; Sun, Kaoxiang; Zhang, Peng (Frontiers in Pharmacology, 2022)
Chemodynamic therapy (CDT), a novel developed approach for cancer treatment, can convert hydrogen peroxide (H2O2) into toxic hydroxyl radicals (•OH) by using Fenton/Fenton-like reaction, to kill tumor cells. However, due to the complexity of the intracellular environment of tumor cells, the therapeutic efficacy of CDT was severely restricted. Recently, combination therapy strategies have become popular approaches for tumor treatment, and there are numerous studies have demonstrated that the CDT-based combination strategies can significantly improve the anti-tumor efficiency of CDT. In this review, the latest achievements of nanosystems for CDT combination therapy and the combined antitumor mechanisms are focused from 2020, as well as the current research limitations and directions are also introduced.